New Evidence Concerning the Professional Situation of Hospital Physicians in Germany - Hannes Spengler (Weekly Report, 2005)
The present report ties in with the recently published weekly report concerning the professional situation of young hospital physicians in Germany. The extensive media coverage points at the explosiveness of this topic. The criticism from different directions ranges up to doubting the scientific basis. Therefore, here we shall take a closer look at the methodical background, in particular the solidity of the underlying data basis. Furthermore, with the new data from the Microcensus 2003, it is now possible to examine the significance of the results calculated in the first report for 2002. However, new findings are in the fore now, especially concerning the working hours of young hospital physicians.
Keywords: 330